IN VITRO AND IN VIVO EVALUATION OF ANTIMICROBIAL AND ANTIOXIDANT POTENTIAL OF STEVIA EXTRACT. - Moselhy, Said S.; Ghoneim, Magdy A.; Khan, Jehan A. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The current trend globally is the utilization of natural products as therapeutic agents given its minimum side effects. The leaves of Stevia contain several active ingredient compounds such as rebaudioside. Stevia extract have been used for many purposes. Active oxygen radicals can induce base modifications, DNA breakage, and intracellular protein crosslink’s. This study was done to evaluate the potential of stevia extract as antibacterial and antioxidants actions. Materials and methods: Antibacterial activity of different extracts of stevia was tested in vitro against different species of bacteria and hepato-protective efficacy was testes in rats injected with CCl4 as hepatotoxic. Results: Acetone extract exhibited antibacterial activity against selected five bacteria species. The acetone extract suppressed the elevation of serum ALT (p <0.05) and AST (p <0.001) activities induced by CCl4. Animals given stevia extract showed prevention against deleterious effects of CCl4 by lowering lipid peroxidation and enhancement of antioxidant activities as SOD and CAT. The protection trial is better than treatment trial. Total phenolic content of aqueous and acetone extracts were found 30 mg and 85 mg gallic /gm extract respectively. While the total flavonoids were 40 mg and 80 mg quercetin/g respectively. The GC-MS analysis showed that monoterpene and indole are the main components. Aqueous extract don’t show any antibacterial activity against the tested strains. The antioxidant properties were attributable to its phenolic content to scavenge free radicals. Conclusion: Acetone extract possess a potent antimicrobial and activity against deleterious effect of CCl4-caused liver damage.